Activation and regulation mechanisms of NOD-like receptors based on structural biology - Ohto, Umeharu (Frontiers in Immunology, 2022)
Innate immunity is a primary defense system against microbial infections. Innate immune pattern recognition receptors (PRRs) play pivotal roles in detection of invading pathogens. When pathogens, such as bacteria and viruses, invade our bodies, their components are recognized by PRRs as pathogen-associated molecular patterns (PAMPs), activating the innate immune system. Cellular components such as DNA and RNA, acting as damage-associated molecular patterns (DAMPs), also activate innate immunity through PRRs under certain conditions. Activation of PRRs triggers inflammatory responses, interferon-mediated antiviral responses, and the activation of acquired immunity. Research on innate immune receptors is progressing rapidly. A variety of these receptors has been identified, and their regulatory mechanisms have been elucidated. Nucleotide-binding and oligomerization domain (NOD)-like receptors (NLRs) constitute a major family of intracellular PRRs and are involved in not only combating pathogen invasion but also maintaining normal homeostasis. Some NLRs are known to form multi-protein complexes called inflammasomes, a process that ultimately leads to the production of inflammatory cytokines and induces pyroptosis through the proteolytic cascade. The aberrant activation of NLRs has been found to be associated with autoimmune diseases. Therefore, NLRs are considered targets for drug discovery, such as for antiviral drugs, immunostimulants, antiallergic drugs, and autoimmune disease drugs. This review summarizes our recent understanding of the activation and regulation mechanisms of NLRs, with a particular focus on their structural biology. These include NOD2, neuronal apoptosis inhibitory protein (NAIP)/NLRC4, NLR family pyrin domain containing 1 (NLRP1), NLRP3, NLRP6, and NLRP9. NLRs are involved in a variety of diseases, and their detailed activation mechanisms based on structural biology can aid in developing therapeutic agents in the future.